Gambaran Perilaku Makan pada Penonton Food Vlog (Video Blog) yang Mengalami Berat Badan Berlebih - Annas Sumeru; Akhyarul Anam; Rizak Tiara Yusan; Ayu Annisa Damayanti (Jurnal Keperawatan Silampari, 2022)
This study aims to obtain information about eating patterns in food vlog viewers who are overweight. This research method is to use quantitative research methods. The results of the study were obtained from 46 participants who were overweight and were analyzed using univariate analysis. Most of them are in the adult age group, aged 26-45 years, amounting to 58.7%. The sex between female and male participants was almost the same, with the proportion of female participants being more, namely 54.3%. Most of the participants had worked. Namely, 78.3% and the majority of those who filled out the questionnaire came from the Javanese tribe of 76.1%. In short, obesity is a health problem that every individual must realize because it can cause other health problems, such as hypertension and diabetes mellitus. Viewers of food vlogs need to get balanced information about proper nutrition, diet, and activity to support optimal health status, especially the body mass index that suits each individual. Keywords: Food Vlog, Social Media, Obesity, Overweight, Youtube